The role of antibodies in Bacille Calmette Guérin-mediated immune responses and protection against tuberculosis in humans: A systematic review. (December 2021) - Bright, Matthew R.; Curtis, Nigel; Messina, Nicole L.
Abstract: Background: The mechanisms underlying Bacille Calmette-Guérin (BCG) vaccine's protective effects against tuberculosis (TB) are incompletely understood but are proposed to involve a predominantly cell-mediated process. However, there is increasing evidence for the involvement of antibodies in the control of Mycobacteria tuberculosis and in the immune response to BCG. Methods: We did a systematic review of studies investigating anti-BCG antibodies in individuals with active or latent TB, and in the response to BCG vaccination. Results: Of 1417 articles screened, 70 were relevant, comprising 52 investigating anti-BCG antibodies in TB and 18 investigating the anti-BCG antibody response to BCG-vaccination. Individuals with active TB have higher levels of anti-BCG antibodies compared with individuals with latent TB or healthy individuals. Antibodies to BCG are present after BCG vaccination. There is some evidence for the in utero transfer of maternal anti-BCG antibodies to infants. Conclusions: BCG vaccination induces a humoral response. Antibodies targeted against BCG and its antigens may play a role in protection against active TB.